1983
DOI: 10.1159/000225687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemotherapy on Taste Sensation in Patients with Disseminated Malignant Melanoma

Abstract: The effect of combination chemotherapy (bleomycin, actinomycin D, vindesine and DTIC) on taste sensation in patients with malignant melanoma was evaluated. Five concentrations of 4 basic tastes (sweet, bitter, sour and salt) were tested. Lowest concentrations of all tastes were subjectively rated more intense after chemotherapy than before. This change was significant for sweet, sour and salt. The highest concentration of sweet was rated significantly less intense following chemotherapy. The discrimination bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 1 publication
0
7
0
2
Order By: Relevance
“…Higher thresholds were found for bitter [85, 86], sweet [86, 87], sour [84, 86], and salty tastes [86]. However, in other studies changes or variations in sensitivity to different concentrations were not observed [82, 83]. Because these studies involved small sample sizes, these contradictory findings might be artefactual.…”
Section: Nutritional Complications Arising From Anti-cancer Therapiesmentioning
confidence: 99%
“…Higher thresholds were found for bitter [85, 86], sweet [86, 87], sour [84, 86], and salty tastes [86]. However, in other studies changes or variations in sensitivity to different concentrations were not observed [82, 83]. Because these studies involved small sample sizes, these contradictory findings might be artefactual.…”
Section: Nutritional Complications Arising From Anti-cancer Therapiesmentioning
confidence: 99%
“…Den vanligast använda metoden är att presentera patienten för olika koncentrationer av de fyra grundsmakerna salt, surt, sött eller bittert. Det ger svar på vilken koncentration av grundsmaken som behövs för att individen ska upptäcka att det smakar något (tröskelvärdet) samt vilken koncentration som behövs för att individen ska kunna identifiera smaken (identifikationstest) (11,76,84). Ännu har inget standardiserat test av den femte grundsmaken umami rapporterats.…”
Section: Testning Av Smak-och Luktförmåganunclassified
“…Mulder et al (84) undersökte patienter diagnostiserade med maligna melanom som behandlades med cytostatika. De fann att lägre koncentrationer av sött, salt och surt skattades ha en högre intensitet efter cytostatikabehandlingen än innan.…”
Section: Testning Av Smak-och Luktförmåganunclassified
“…The few studies that have investigated TSCs among patients receiving cancer chemotherapy have focused on physiological tests of taste and smell sensitivity [3,19,21] or prevalence of disturbance [10,25] rather then on how these chemosensory changes affect patients' daily lives. While such physiological knowledge is important in developing approaches to prevent or treat disturbances, knowledge about patients' experiences of TSCs is also needed to enable support during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%